1993
DOI: 10.1177/000456329303000408
|View full text |Cite
|
Sign up to set email alerts
|

Dual Analyte Immunoassay in Neural Tube Defect and Down's Syndrome Screening: Results of a Multicentre Clinical Trial

Abstract: SUMMARY. We report a multicentre clinical field trial of a novel dual analyte enzyme immunoassay method for the simultaneous measurement of alpha-fetoprotein (AFP) and free (j-human choriogonadotropin (hCG) in the same micro titre well. The assay was shown to have good technical performance in the hands of all trial centres, with between assay coefficients of variation better than 10% for both analytes across the whole of the assay ranges. The method compared well with single analyte measuring procedures and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
9
0

Year Published

1993
1993
1998
1998

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 13 publications
7
9
0
Order By: Relevance
“…The results of our prospective study in which we have achieved a detection rate for Down's syndrome of 69% with a 5-2% false positive rate confirm the data published in retrospective studies8 [11][12][13] and establish further the benefits of screening by using free 1 human chorionic gonadotrophin and at fetoprotein. We have indicated that once again detection rates may be better earlier in gestation and that in women under 30 the detection rate with this approach is as good as that achieved in one study of the triple test when applied prospectively to women of all ages.7 Table II summarises the results and those from four major prospective studies of the triple test.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The results of our prospective study in which we have achieved a detection rate for Down's syndrome of 69% with a 5-2% false positive rate confirm the data published in retrospective studies8 [11][12][13] and establish further the benefits of screening by using free 1 human chorionic gonadotrophin and at fetoprotein. We have indicated that once again detection rates may be better earlier in gestation and that in women under 30 the detection rate with this approach is as good as that achieved in one study of the triple test when applied prospectively to women of all ages.7 Table II summarises the results and those from four major prospective studies of the triple test.…”
Section: Discussionsupporting
confidence: 87%
“…If one averages the performance of the remaining studies of the triple test the detection rate by using free 13 human chorionic gonadotrophin is about 10% higher. We have consistently shown this difference in retrospective studies,12 13 and by using a modelling approach, Cuckle and Lilford have also shown an 8-10% higher detection rate when using free ,B human chorionic gonadotrophin.3' Wald and Hackshaw have recently suggested that the benefits of free 1 human chorionic gonadotrophin screening may not be achievable in practice and have disputed the projected detection rates based on their own claims3' which have been further refuted by Cuckle and Lilford32 and by Spencer et al33 The detection rates in our study and those unpublished studies summarised by Spencer et aP3 are totally consistent with the earlier direct observation of an 8-10% improvement in detection rate when using the free 1 approach rather than the triple test. 8 Haddow et al estimated the number of cases of Down's syndrome in the study population by taking the number of subjects at each year age band and multiplying this by the age specific risk of Down's syndrome in the second trimester.23 They then proceeded to back calculate from published retrospective estimates of detection rates of Down's syndrome to find the number of cases likely to reach term among the group of women who were classified as not at increased risk.…”
Section: Discussionsupporting
confidence: 66%
“…Analyzing the group of patients under 35 and over 35 years separately, the screen positive rates were 3.1 and 23.3%, respectively, which is consistent with data published in other prospective studies [6,12]. It must be taken into consideration that the overall detection rate should not be equalized with the detection efficiency of all ages.…”
Section: Discussionsupporting
confidence: 87%
“…The efficiency is similar to the other studies that use the same cut-off risk and include the large proportion (620 %) of pregnancies in women aged 35 or over [10]. It is well known that the detection rates are strongly dependent on the age distribution of the population being screened [11,12]. Based on the maternal age distribution of our screened population, we expected that there would be 9 cases of Down's syndrome at second-trimester pregnancy among the patients screened.…”
Section: Discussionsupporting
confidence: 76%
“…In the late 1980s, a triple screen test was developed, comprising hCG -fetoprotein, and unconjugated oestriol, for detecting Down syndrome and other aneuploidies in second-trimester pregnancies (Bogart et al, 1987;Wald et al, 1988;Canick, 1990). More recently, serum free -subunit tests and free -subunit/ -fetoprotein combinations have been introduced as alternative tests for screening second-trimester pregnancies (Macri et al, 1990;Spencer et al, 1991;Spencer et al, 1993). The best free -subunit combination, or the optimal triple screen test, however, detects only 60-70 per cent of Down syndrome cases, with a 5 per cent false positive rate.…”
Section: Introductionmentioning
confidence: 99%